Clinical variability of neurofibromatosis 1: A modifying role of cooccurring PTPN11 variants and atypical brain MRI findings. Issue 5 (17th August 2021) - D'Amico, Alessandra; Rosano, Carmen; Pannone, Luca; Pinna, Valentina; Assunto, Antonia; Motta, Marialetizia; Ugga, Lorenzo; Daniele, Paola; Mandile, Roberta; Mariniello, Lucio; Siano, Maria Anna; Santoro, Claudia; et al.
Abstract: Neurofibromatosis 1 (NF1) is a disorder characterized by variable expressivity caused by loss‐of‐function variants in NF1, encoding neurofibromin, a protein negatively controlling RAS signaling. We evaluated whether concurrent variation in proteins functionally linked to neurofibromin contribute to the variable expressivity of NF1. Parallel sequencing of a RASopathy gene panel in 138 individuals with molecularly confirmed clinical diagnosis of NF1 identified missense variants in PTPN11, encoding SHP2, a positive regulator of RAS signaling, in four subjects from three unrelated families. Three subjects were heterozygous for a gain‐of‐function variant and showed a severe expression of NF1 (developmental delay, multiple cerebral neoplasms and peculiar cortical MRI findings), and features resembling Noonan syndrome (a RASopathy caused by activating variants in PTPN11 ). Conversely, the fourth subject, who showed an attenuated presentation, carried a previously unreported PTPN11 variant that had a hypomorphic behavior in vitro. Our findings document that functionally relevant PTPN11 variants occur in a small but significant proportion of subjects with NF1 modulating disease presentation, suggesting a model in which the clinical expression of pathogenic NF1 variants is modified by concomitant dysregulation of protein(s) functionally linked to neurofibromin. We also suggest targeting of SHP2 function as an approach to treat evolutive complications of NF1. Abstract :